Brookville, Saline County - Shaw, Conner (Kansas State University, The Chapman Center for Rural Studies, 2012)
Once a vibrant town, filled with hard working people who made their way west looking to start a new life, Brookville has now become a quiet, low density community. As shown in this research, we will begin to understand why and how this happened. This paper includes early maps, research, and photographs of Brookville, located in Saline County, Kansas.
Conner Shaw, “Brookville, Saline County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/104.
Keywords: Brookville; Central Hotel; Charles Lindbergh; John Crittenden; Saline County; Union Pacific Railroad